1988
DOI: 10.1073/pnas.85.10.3284
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 3 stimulates proliferation via protein kinase C activation without increasing inositol lipid turnover.

Abstract: Interleukin 3 (IL-3) is required for the survival and proliferation of the FDCP-Mix 1 multipotent stem cell line. IL-3 or phorbol esters can rapidly translocate protein kinase C from a cytosolic to a membrane-bound form in these cells. Phorbol esters were able to partially replace the requirement of FDCP-Mix 1 cells for IL-3. Down-modulation of protein kinase C levels by chronic treatment with phorbol ester markedly reduced the ability of the cells to proliferate in response to either IL-3 or phorbol esters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 25 publications
(23 reference statements)
3
48
0
Order By: Relevance
“…This protein was also similarly phosphorylated in response to pharmacological activators of PK-C. We postulated that PK-C, or an analogous kinase system, was involved in the biological action of IL3 and G-CSF and that p68 phosphorylation might represent a point of convergence for several signal transduction pathways leading to proliferation. Recently, Whetton et al [29] have shown that IL3 may activate a PK-C-like system in the absence of detectable phosphoinositol 4,5-bisphosphate hydrolysis, suggesting an atypical mechanism activating PK-C.…”
Section: Discussionmentioning
confidence: 99%
“…This protein was also similarly phosphorylated in response to pharmacological activators of PK-C. We postulated that PK-C, or an analogous kinase system, was involved in the biological action of IL3 and G-CSF and that p68 phosphorylation might represent a point of convergence for several signal transduction pathways leading to proliferation. Recently, Whetton et al [29] have shown that IL3 may activate a PK-C-like system in the absence of detectable phosphoinositol 4,5-bisphosphate hydrolysis, suggesting an atypical mechanism activating PK-C.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mltogemc slgnalhng pathway actlvatcd by IL3 m 32D cells IS largely unknown, several tndlcatlons point to protcm kmase C as a possible mediator of the IL3 effect on plohferdtlon [7,8]. Smce actlvatlon of protein kmase C in response to growth factors IS behcved to bc achlcved by the generatlon of diacylglyccrol, we rncasurcd dlacylglycerol and other second mcssengcr fortnatIon III response to different agent\ It is worth noting that the IL3 effect was studlcd in wild-type 204 32D cells, whereas the effects of EGF, PDGF, and CSF-1 were studied m transfectants expressing their respectlve receptor [a-41 Control experiments showed that transfcctants expressmg foreign growth factor reccptols retained their ability to respond to IL3 m the same way as wild-type cells did (not shown) Table I shows that IL3, EGF, and CSF-1 stimulated the formation of dlacylglycerol to a slmllar extent; the late of dlacylglycerol formation was comparable to that reported m fibroblasts stnnulated by potent growth factors [I35 This effect was dose-and time-dependent, time-course expcrlments showed that maximal accumulation of dlacylglycerol occulted within 10 mm from stlmulatlon…”
Section: Resultsmentioning
confidence: 99%
“…!& abl, and src[l]) or by mtroductlon of foreign growth factor receptor genes followed by stimulation with the appropriate growth factor Thus, we demonstrated that growth factors as diverse as epldelmal growth factor (EGF), platelet-derived growth facto1 (PDGF), and colony stlmulatmg factor-l (CSF-1) could sustain 32D cell prohferatlon once the receptor gene had been introduced into cells [2][3][4] Since such a vancty of growth factors and oncoprotems could lead to a slmllar feature (abrogation of IL3 requirement), we reasoned that common signal transducmg elements were activated by IL3, EGF, PDGF, CSF-I, and during oncogcne-induced transformation However, it is known that each one of these factors rehes on different signal transducing mechanisms to elicit mltogemc responses. EGF and PDGF stimulate the turnover of mosltol hplds with formation of dlacylglycerol and tnositol phosphates (for review see [5]); CSF-1 seems to activate phosphdtidylmositol-3 kmase in macrophages and fibroblasts without triggering mosltol hpld hydrolysis [G]; IL3, on the other hand, activates protcm klnuse C (PKC) without mcreasmg inositol lipid turnover [7,8] …”
Section: Introductionmentioning
confidence: 99%
“…This may have been due to the ability of CSF-1 to stimulate PKC through a different mechanism than LPS, which was not affected by L. donovani. For example, multi-CSF (interleukin-3) stimulates PKC in a manner independent of inositol lipid turnover (37) We have also examined TNF gene expression in L. donovani-infected macrophages. Products of the cyclooxygenase pathway were responsible for the suppression of LPS-induced TNF gene expression, since indomethacin abrogated the impairment of TNF gene expression in infected cells.…”
mentioning
confidence: 99%